Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.bbrc.2017.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Roles of antibodies to influenza A virus hemagglutinin, neuraminidase, and M2e in conferring cross protection

Abstract: Although neuraminidase (NA) is the second major viral glycoprotein of influenza virus, its immune mechanism as a vaccine target has been less considered. Here we compared the properties of antibodies and the efficacy of cross protection by N1 and N2 NA proteins, inactivated split influenza vaccines (split), and tandem repeat extracellular domain M2 on virus-like particles (M2e5x VLP). Anti-NA immune sera could confer better cross-protection against multiple heterologous influenza viruses correlating with NA in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Previous studies have shown that Fc-FcγR interactions contribute little to the protection of mice treated with anti-A(H1N1)pdm09 polyclonal serum against homologous challenge (19). Initially, we sought to confirm this phenotype in the context of a protective polyclonal anti-NA immune serum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that Fc-FcγR interactions contribute little to the protection of mice treated with anti-A(H1N1)pdm09 polyclonal serum against homologous challenge (19). Initially, we sought to confirm this phenotype in the context of a protective polyclonal anti-NA immune serum.…”
Section: Resultsmentioning
confidence: 99%
“…Whether this contributes to protection in vivo is unknown. Kim et al (19) have shown that FcγR knockout (KO) mice lose slightly more weight than wild-type (WT) counterparts when infected with A(H1N1)pdm09 preincubated with polyclonal sera raised to recombinant N1 NA. Finally, Kawaoka and colleagues recently demonstrated that human A(H1N1)pdm09 anti-NA antibodies that target the lateral side of the NA head not only protect in an Fc-dependent manner but may also drive antigenic drift in the lateral portion of the NA head (20).…”
Section: Introductionmentioning
confidence: 99%
“…Although a truly stratifying correlation between in vitro activity and in vivo activity was not resolved, 1086F8 and 1092D4, which exhibited the greatest in vivo activity against B/Brisbane/60/2008 virus, including suppressing the virus to below detectable levels in several mice, were the most potent hMAbs in inhibiting B/Brisbane/60/2008 virus replication in vitro (IC 50 , <0.5 μg/ml) but were not superior to the other hMAbs in their ELLA activity. Several animal studies demonstrated previously that Fc-mediated effector functions such as ADCC substantially contribute to the in vivo antiviral activity of NA-specific antibodies (2730). Our study did not attempt to define the relative scontribution of Fc-mediated antibody functions; however, our resulting panel of NA-specific hMAbs is likely to serve future utility in defining mechanisms of action of NA Ab-mediated protection.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that immune sera against NA and M2e were superior in terms of improving heterosubtypic protection and survival than anti-HA Abs induced by the split seasonal vaccine. Interestingly, the co-administration of NA and M2e5XVLP immune sera gave rise to a synergistic heterologous protection effect (107).…”
Section: Antibodies Against Iav External Proteinsmentioning
confidence: 99%